Reconstruction of Basal Cell Carcinoma over Face by Facial Flaps –Study of 30 Cases - Ghosh, Subrata; Chowdhury, Milon Kumar; Biswas, Nripendra Nath; Sarkar, Sunandita; Sarkar, Anindita; Chandra, Pampa (TAJ: Journal of Teachers Association, 2018)
Background: Basal cell carcinoma (BCC) is the most common skin cancer.85% of BCC are located in the head and neck area, of which 30% on the nose. After excision of BCC on the face, the options of treatment for a skin defect are variable. Many surgeons prefer to use a local flap rather than skin graft or free flap for small or moderately sized circular defects after excision of BCC on the face. Methods: All of the patients were histopathologically diagnosed as Basal cell carcinoma, thirty patients underwent various flaps like V-Y advancement flap, bilobed flap, forehead flap, nasolabial flap, glabellar flap repair over 3 years, between January 2014 to December 2016. We observed post-operative complications as flap loss either partial or complete, wound dehiscence, hematoma and wound infection and recurrence of carcinoma. The cosmetic outcome of the face also evaluated. Results: There were 19 men and 11 women. The age ranged from 48 to 73 years with a mean age of 62 years. The causes were BCC in all cases. The tumour locations were the face in all patients. All of the flaps survived, but in one case recurrence of BCC occur, which was managed surgically. Post-operative recovery was very nice. Conclusions: Our study shows facial flaps give nice result and first choice for facial reconstruction in BCC of face. Most defects can best closed by various facial flaps and outstanding functional and cosmetic results can be achieved. TAJ 2017; 30(2): 20-25